2020
DOI: 10.3390/plants9030397
|View full text |Cite
|
Sign up to set email alerts
|

Flower Colour Polymorphism, Pollination Modes, Breeding System and Gene Flow in Anemone coronaria

Abstract: The flower colour of Anemone coronaria (Ranunculaceae) is a genetically inherited trait. Such intra-specific flower colour polymorphism might be driven by pollinators, other non-pollinating agents, or by abiotic factors. We investigated the genetic relations among red, white and purple-blue flower colour morphs growing in 10 populations of A. coronaria in Israel, in relation to their breeding system, pollination modes, differential perception by bees and visitors’ behaviour. Flowers of these three morphs diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 92 publications
(73 reference statements)
0
5
0
Order By: Relevance
“…The strategy of patterned flowers does not show phylogenetic signal, and a nonnegligible number of species showed both strategies, suggesting that this floral feature is a colour signal widespread among angiosperms (Lunau et al, 2017). Although flower colour is often considered an evolutionarily labile floral trait (Dafni et al, 2020; Ortiz et al, 2021; Reverté et al, 2016), we have found that UV‐red colour presented a significant phylogenetic signal. Taking together, our results suggest that the prevalence of hymenopterans pollination in red‐flowered species of the Mediterranean Basin is not the product of a single coevolutionary interaction between species, but rather the result of diverse evolutionary and ecological processes acting at the species and community level (Dalrymple et al, 2020; Kemp et al, 2019; Narbona et al, 2018; Strauss & Whitall, 2006).…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…The strategy of patterned flowers does not show phylogenetic signal, and a nonnegligible number of species showed both strategies, suggesting that this floral feature is a colour signal widespread among angiosperms (Lunau et al, 2017). Although flower colour is often considered an evolutionarily labile floral trait (Dafni et al, 2020; Ortiz et al, 2021; Reverté et al, 2016), we have found that UV‐red colour presented a significant phylogenetic signal. Taking together, our results suggest that the prevalence of hymenopterans pollination in red‐flowered species of the Mediterranean Basin is not the product of a single coevolutionary interaction between species, but rather the result of diverse evolutionary and ecological processes acting at the species and community level (Dalrymple et al, 2020; Kemp et al, 2019; Narbona et al, 2018; Strauss & Whitall, 2006).…”
Section: Discussionmentioning
confidence: 49%
“…The strategy of patterned flowers does not show phylogenetic signal, and a nonnegligible number of species showed both strategies, suggesting that this floral feature is a colour signal widespread among angiosperms (Lunau et al, 2017). Although flower colour is often considered an evolutionarily labile floral trait (Dafni et al, 2020;Ortiz et al, 2021;Reverté et al, 2016), we have found that UV-red colour presented a significant phylogenetic signal.…”
Section: Con Clus Ionsmentioning
confidence: 57%
“…Plants were cultivated in clay pots (20 cm in diameter and 15 cm in depth) using tree barks as substrate. To reduce the possible effects of environment on color differences ( Schemske and Bierzychudek, 2001 ; Dafni et al, 2020 ), individuals were cultivated in the same natural light and temperature conditions and were watered at least twice a day.…”
Section: Methodsmentioning
confidence: 99%
“…Flower colouration polymorphism refers to the variation in flower colours within or between natural populations of the same species (Dafni et al, 2020). Although the flower colour is diverse throughout flowering plants, variation within a species is uncommon.…”
Section: Discussionmentioning
confidence: 99%